Analysis of Leaching Rate of Heavy Metals from Fly Ash at Varying Leachant pH & Cumulative Liquid to Solid Ratios - Tobby, Micheal Agwe; Sharma, S. N.; Pandey, Govind (i-manager’s Journal on Material Science, 2021)
Fly ash (FA) is a particulate matter consisting of finely divided, non-combustible particles obtained from the flue gases arising from combustion of coal, accounts for over 80% of the total ash produced during coal combustion. In 2018 alone, about 780 million tons of FA has been generated globally, of which voluminous quantity remained unutilized, hence dumped into the environment. This continued disposal of FA into the environment makes the heavy metals contained therein to move out in the leachate generated, polluting the soil, surface and ground water sources among others. In this study, 5 sets of leaching test columns were packed with an equal quantity of air dried fly ash samples and each of them leached with leachant of pH 5.87, 6.08, 6.41, 6.46 and 7.01 and eluate from each column collected at cumulative liquid to solid (L/S) ratios in l/kg of 0.1, 0.2, 0.5, 1.0 and 2.0. Analysis of the eluate for Copper (Cu), Selenium (Se), Zinc (Zn), Cadmium (Cd), Lead (Pb), Nickel (Ni), Chromium (Cr) and Arsenic (As), revealed that the concentrations of Se at Selenium L/S of 0.1 for leachant pH of 5.87, 6.41 and 7.01, exceeded the allowable limits for non-hazardous wastes disposal into the landfills.